Active loading of pectin hydrogels for targeted drug delivery - Vesvoranan, Oraya; Liu, Betty; Zheng, Yifan; Wagner, Willi Linus; Sutlive, Joseph; Chen, Zi; Khalil, Hassan A.; Ackermann, Maximilian; Mentzer, Steven J. (Polymers, 2023)
Hydrogels provide a promising method for the targeted delivery of protein drugs. Loading the protein drug into the hydrogel free volume can be challenging due to limited quantities of the drug (e.g., growth factor) and complex physicochemical properties of the hydrogel. Here, we investigated both passive and active loading of the heteropolysaccharide hydrogel pectin. Passive loading of glass phase pectin films was evaluated by contact angles and fractional thickness of the pectin films. Four pectin sources demonstrated mean contact angles of 88° with water and 122° with pleural fluid (p < 0.05). Slow kinetics and evaporative losses precluded passive loading. In contrast, active loading of the translucent pectin films was evaluated with the colorimetric tracer methylene blue. Active loading parameters were systematically varied and recorded at 500 points/s. The distribution of the tracer was evaluated by image morphometry. Active loading of the tracer into the pectin films required the optimization of probe velocity, compression force, and contact time. We conclude that active loading using pectin-specific conditions is required for the efficient embedding of low viscosity liquids into pectin hydrogels.